Reposition of a Bi-caval Dual Lumen ECMO cannula using a trans-femoral lasso - Robert Jan Houmes; Thomas Krasemann; Claudia M.G. Keyzer-Dekker (Elsevier, 2020)
Veno-venous double lumen Extracorporeal membrane oxygenation (VVDL-ECMO) in neonates and infants for viral pneumonia is a well-established therapy. However even after initial correct positioning of the VVDL-ECMO cannula, there is a risk of unexpected malpositioning of this cannula during the ECMO run. We report a case of reposition of a 16-French Avalon Elite Bi-caval Dual Lumen cannula from its malposition in the right atrium to its correct position in the inferior venous cava. The procedure was achieved by interventional catheter techniques using a goose neck snare and was done without ECMO-flow interruption. Keywords: Infant, Dual lumen cannula, VVDL ECMO